Optimization of Load Ranking and Load Shedding in a Power System Using the Improved AHP Algorithm - Le, T. N.; Nguyen, H. M. V.; Nguyen, T. A.; Phung, T. T.; Phan, B. D. (Engineering, Technology & Applied Science Research, 2022)
This paper proposes a method of load ranking and load shedding in a power system based on the calculation of the priority weighting continuity of the power supply of loads and the improved AHP algorithm. The proposed method applies the theories of covariance between objects, correlation, and fuzzy preference to develop a fuzzy preference correlation matrix based on the percentage of Vital Load, Semi Vital Load, and Non-Vital Load at each load bus. This matrix replaces the judgment matrix of the traditional AHP algorithm to form the criteria layers and scheme layers of the problem. The priority weighting continuity of the power supply of loads is continuously calculated and updated according to the load profile and is used to distribute the load shedding power to each load bus. This distribution optimizes the objective function and maximizes the load benefits, thereby minimizing the damages due to load shedding. The traditional AHP method and the proposed method are applied to the IEEE 30 bus system and the result comparison demonstrates the effectiveness of the proposed method.